Savior or not: ADAM17 inhibitors overcome radiotherapy-resistance in non-small cell lung cancer - Ieguchi, Katsuaki; Maru, Yoshiro (Journal of Thoracic Disease, 2016)
According to WHO cancer report in 2015, lung cancer is the most leading cause of cancer-associated death and accounts for approximately 20% of whole cancer-related death. The 5-year survival rate is less than 30% and the average of other types of cancer such as colon, breast, and prostate cancer in stage II and more advanced stages. Therefore, lung cancer is recognized as a poor prognostic cancer and needs an establishment of efficient therapy. Anti-EGFR drugs dramatically reduce tumor growth for non-small cell lung cancer (NSCLC) with EGFR mutations but the clinical outcome has been still disappointing because of against treatment by genetic alterations emerged as clinical problems (1). Moreover, it was reported that a combination therapy by using anti-EGFR drugs and ionizing radiation (IR) has provided no additive beneficial outcome in those patients (2). Accordingly, targeting other EGF signaling-related molecules would be breakthrough for anti-EGFR therapy-resistant NSCLC and is highly demanded.